2019
DOI: 10.2147/opth.s185287
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brittle cornea syndrome: current perspectives</p>

Abstract: Brittle cornea syndrome (BCS) is a rare autosomal recessive connective tissue disorder characterised by severe corneal thinning, with the major ocular risk being spontaneous ocular perforation due to progressive stromal thinning and ectasia. It is a complex condition with limited treatment options. The purpose of this review is to highlight the difficulties associated with the condition and examine the available published evidence with regards to management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(55 citation statements)
references
References 48 publications
(75 reference statements)
2
53
0
Order By: Relevance
“…Corneal edema resulting from breaks in the Descemet's membrane may occur, and extremely thin corneas are prone to rupture after minor injury ( Burkitt Wright et al, 2013 ). No longitudinal studies of CCT in BCS have been reported, probably due to the young age at which corneal perforations occur {mean age of published cases with rupture, 4.3 years of age [range 1.5-19 years ( Walkden et al, 2019 )]}. None of our BCS mice, aged up to 9 months, suffered from cornea rupture, and only one case of corneal edema was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Corneal edema resulting from breaks in the Descemet's membrane may occur, and extremely thin corneas are prone to rupture after minor injury ( Burkitt Wright et al, 2013 ). No longitudinal studies of CCT in BCS have been reported, probably due to the young age at which corneal perforations occur {mean age of published cases with rupture, 4.3 years of age [range 1.5-19 years ( Walkden et al, 2019 )]}. None of our BCS mice, aged up to 9 months, suffered from cornea rupture, and only one case of corneal edema was recorded.…”
Section: Discussionmentioning
confidence: 99%
“…It also affects the development of retinal microvasculature and Bruch's membrane. [ 5 ] However, these abnormal retinal microvascular changes are evident only on immunohistochemistry. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 3 ] Mutations in PRDM5 produces abnormal fibrillar collagen affecting corneal integrity and alterations in retinal capillaries and Bruch's membrane. [ 5 ] Type 1 BCS has wrinkled skin involving palms and soles with scarring, molluscoid pseudotumors, and chestnut-coloured hair. [ 6 7 ] Whereas, in Type 2 the skin is soft with easy bruisabilty.…”
mentioning
confidence: 99%
“…I have read with great interest the review article by Walkden et al on “Brittle Cornea Syndrome: Current Perspectives” 1. I would like to express my appreciation to the authors for an elaborate and comprehensive review of this complex disease which has devastating complications.…”
Section: Dear Editormentioning
confidence: 99%